2013
DOI: 10.1103/physrevlett.110.267001
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Enhanced Pinning of Magnetic Vortices in Type-II Superconductors by Conformal Crystal Arrays

Abstract: Conformal crystals are non-uniform structures created by a conformal transformation of regular two-dimensional lattices. We show that gradient-driven vortices interacting with a conformal pinning array exhibit substantially stronger pinning effects over a much larger range of field than found for random or periodic pinning arrangements. The pinning enhancement is partially due to matching of the critical flux gradient with the pinning gradient, but the preservation of the sixfold ordering in the conformally tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 54 publications
(39 reference statements)
7
95
0
Order By: Relevance
“…Our experiments have been carried out on a 200-nm-thick superconducting Pb film with randomly distributed pinning centres. There exist several methods to introduce pinning centres in superconductors, such as lithographically made well-controlled pinning sites 25,26 , ionirradiation-introduced point defects 27 , grain boundaries 28 , thickness variations 29 and so on. Most of these methods lead to the suppression of the superconducting order parameter at the pinning sites that makes them energetically favourable for vortices to localize on 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Our experiments have been carried out on a 200-nm-thick superconducting Pb film with randomly distributed pinning centres. There exist several methods to introduce pinning centres in superconductors, such as lithographically made well-controlled pinning sites 25,26 , ionirradiation-introduced point defects 27 , grain boundaries 28 , thickness variations 29 and so on. Most of these methods lead to the suppression of the superconducting order parameter at the pinning sites that makes them energetically favourable for vortices to localize on 30 .…”
Section: Resultsmentioning
confidence: 99%
“…The appeal and advantage of superconducting systems is that the size and number of the particles can be tuned by changing the temperature and the magnetic field, respectively. In addition, the flexibility in the design and fabrication of artificial vortex traps in superconducting films has stimulated, during the past decade, an in-depth investigation of the interplay between pinning landscape and vortex pattern symmetry [16], influence of the pinning center's size and period [17][18][19][20], vortex rectification on a kagome-like array [21], competition between ordered and disordered defects [22][23][24], or pinning energy dispersion [25,26], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…There are conditions where the conformal array is not as optimal as uniform triangular arrays, such as at integer matching fields where the gradient in the conformal arrays can prevent formation of a completely commensurate state. Initial simulations showed that conformal pinning arrays produced enhanced pinning compared to uniform random arrays, random arrays with a gradient, and periodic pinning arrays at non-matching fields, particularly at fields where there are more vortices than pinning sites [23,24]. Experiments indicated that the triangular pinning arrays produced stronger pinning than the conformal arrays below the first matching field, while the conformal pinning array generated stronger pinning at higher fields [28].…”
Section: Introductionmentioning
confidence: 99%